2008
DOI: 10.1161/circulationaha.107.741579
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Survival and Mental and Psychomotor Outcomes After the Norwood Procedure

Abstract: Background-The Norwood procedure for stage 1 palliation of hypoplastic left heart syndrome is performed with either the modified Blalock-Taussig (MBTS) or the right ventricle-to-pulmonary artery (RVPA) shunt. In our institution, surgical practice changed from use of the MBTS to use of the RVPA shunt in 2002. We analyzed survival and mental and psychomotor outcomes of the 2 consecutive surgical eras. Methods and Results-Between September 1996 and July 2005, 94 neonates with hypoplastic left heart syndrome under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 49 publications
(46 reference statements)
0
31
1
Order By: Relevance
“…In contrast, Atallah et al did find a difference in PDI at 2 years between those treated with an RVPAS (mean PDI=78) and those with a MBTS (mean PDI=67). 22 This finding however was based on an observational cohort, with the shunt type changing by era, so that secular changes in other practices may have confounded this study finding.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, Atallah et al did find a difference in PDI at 2 years between those treated with an RVPAS (mean PDI=78) and those with a MBTS (mean PDI=67). 22 This finding however was based on an observational cohort, with the shunt type changing by era, so that secular changes in other practices may have confounded this study finding.…”
Section: Discussionmentioning
confidence: 88%
“…7 Importantly, these studies have identified few modifiable risk factors for adverse neurodevelopmental outcomes. [7][8][9] In addition, these studies usually derive from single centers and are limited by small sample size.…”
Section: What This Study Addsmentioning
confidence: 99%
“…All invited investigators agreed to submit data for this analysis. 8,9,[15][16][17][18][19][20][21][22][23][24] …”
Section: Identification Of Participating Institutionsmentioning
confidence: 99%
“…In the Boston Circulatory Arrest Study, length of stay was independently associated with worse cognitive function at 8 years of age, even after adjustment for factors related to the length of stay (e.g., sepsis, low cardiac output) or cognitive outcomes (e.g., maternal education, socioeconomic status) (76). Virtually all studies reporting short and longer term neurodevelopmental outcomes have two consistent factors independently related to worse outcomes: increased length of stay and lower socioeconomic status (77, 80, 108110). While some aspects of length of stay may not be modifiable, many units are now actively investigating strategies to reduce length of stay (e.g., timing of surgery, early extubation, minimizing delayed sternal closure, etc.)…”
Section: Length Of Staymentioning
confidence: 99%